Three new species of Cylloepus Erichson (Insecta: Coleoptera: Elmidae) from Southeastern Brazil - Sampaio, Brunno Henrique Lanzellotti; Da Silva Dos Passos, Maria Inês; Ferreira-Jr., Nelson (Zootaxa, 2011)
The genus Cylloepus is found in the Nearctic and Neotropical Regions and currently represented by 52 species. Twenty species are recorded from Brazil, and three of them from Rio de Janeiro State. Here three new species of Cylloepus are described—Cylloepus quinquecarinatus sp. nov., Cylloepus nessimiani sp. nov., and Cylloepus friburguensis sp. nov. All were collected in the Rio Macaé Basin, Rio de Janeiro State, southeastern Brazil.